Cervical cord myelin abnormality is associated with clinical disability in multiple sclerosis. (December 2021) - Lee, Lisa Eunyoung; Vavasour, Irene M; Dvorak, Adam; Liu, Hanwen; Abel, Shawna; Johnson, Poljanka; Ristow, Stephen; Au, Shelly; Laule, Cornelia; Tam, Roger; Li, David KB; Cross, Helen; et al.
Background: Myelin water imaging (MWI) was recently optimized to provide quantitative in vivo measurement of spinal cord myelin, which is critically involved in multiple sclerosis (MS) disability. Objective: To assess cervical cord myelin measurements in relapsing-remitting multiple sclerosis (RRMS) and progressive multiple sclerosis (ProgMS) participants and evaluate the correlation between myelin measures and clinical disability. Methods: We used MWI data from 35 RRMS, 30 ProgMS, and 28 healthy control (HC) participants collected at cord level C2/C3 on a 3 T magnetic resonance imaging (MRI) scanner. Myelin heterogeneity index (MHI), a measurement of myelin variability, was calculated for whole cervical cord, global white matter, dorsal column, lateral and ventral funiculi. Correlations were assessed between MHI and Expanded Disability Status Scale (EDSS), 9-Hole Peg Test (9HPT), timed 25-foot walk, and disease duration. Results: In various regions of the cervical cord, ProgMS MHI was higher compared to HC (between 9.5% and 31%, p  ⩽ 0.04) and RRMS (between 13% and 26%, p  ⩽ 0.02), and ProgMS MHI was associated with EDSS ( r  = 0.42–0.52) and 9HPT ( r  = 0.45–0.52). Conclusion: Myelin abnormalities within clinically eloquent areas are related to clinical disability. MWI metrics have a potential role for monitoring subclinical disease progression and adjudicating treatment efficacy for new therapies targeting ProgMS.